Coliving of de financialisering van Brusselse huizen - Charlotte Casier (Brussels Studies, 2023)
Coliving in Brussels consists in the renting of rooms in a building with shared spaces and services by private companies. With its furnished and flexible “all-inclusive” formula, this niche market is growing rapidly and is aimed especially at young expatriates in Brussels. The analysis of the recent development of this type of housing supply shows how the financialisation of the private residential rental sector is based on the creation of new products designed in order for investors to inject their capital easily and obtain high returns. In Brussels, coliving exists mainly in single-family houses in the south-east neighbourhoods of the inner ring.